Internet health scams—Developing a taxonomy and risk‐of‐deception assessment tool. (6th September 2018) - Garrett, Bernie; Murphy, Sue; Jamal, Shahin; MacPhee, Maura; Reardon, Jillian; Cheung, Winson; Mallia, Emilie; Jackson, Cathryn
Abstract: The prevalence of health scams in Canada is increasing, facilitated by the rise of the Internet. However, little is known about the nature of this phenomena. This study sought to methodically identify and categorise Internet‐based Health Scams (IHS) currently active in Canada, creating an initial taxonomy based on systematic Internet searches. A five‐step Delphi approach, comprised of a multidisciplinary panel of health professionals from the University of British Columbia, in Vancouver, Canada, was used to establish consensus. The resulting taxonomy is the first to characterise the nature of IHS in North America. Five core areas of activity were identified: body image products, medical products, alternative health services, healthy lifestyle products, and diagnostic testing services. IHS purveyors relied on social expectations and psychological persuasion techniques to target consumers. Persuasion techniques included social engagement, claims of miraculous effects, scarcity, and the use of pseudoscientific language. These techniques exploited personality traits of sensation seeking, needing self‐control, openness to taking risks, and the preference for uniqueness. The data gathered from the taxonomy allowed the Delphi panel to develop and pilot a simple risk‐of‐deception tool. This tool is intended to help healthcare professionals educate the public about IHS. It is suggested that, where relevant, healthcare professionals include a general discussion of IHS risks and marketing techniques with clients as a part of health promotion activities.